Association of Mu-Opioid Receptor(MOR) Expression and Opioids Requirement With Survival in Patients With Stage I-III Pancreatic Ductal Adenocarcinoma - Zhang, Hao; Qu, Mengdi; Gorur, Aysegul; Sun, Zhirong; Cata, Juan P.; Chen, Wankun; Miao, Changhong (Frontiers in Oncology, 2021)
Background: The use of opioids in patients with metastatic pancreatic ductal adenocarcinoma (PDAC) is associated with shorter survival and not dependent on the expression of the mu-opioid receptor (MOR). The role of opioid use and MOR expression in stage I-III PDAC has not been investigated. Methods: We conducted retrospective study in patients with stage I-III PDAC. MOR expression and OPRM1 gene expression in tumour tissue and non-tumour tissue was measured.Primary endpoints were overall survival (OS) and disease-free survival (DFS). Secondary endpoints included perineural invasion, intraoperative sufentanil consumption, and length of stay. We performed a subgroup group analysis to evaluate the interaction between levels of MOR expression, amount of opioids use (high versus low) and its association with survival. Results: A total of 236 patients were enrolled in this study.There were no significantly difference in OS rates in patients with high versus low levels of MOR (1-year OS: 65.2% versus 70.6%, P=0.064; 3-year: 31.4 % versus 35.8 %, P=0.071; 5-year: 19.4% versus. 16.2%, P=0.153, respectively) in the tumours. The DFS rates between the groups were no significantly difference. Of note, a high expression of MOR combined with high opioid consumption was associated with poor prognosis in stage I-III PDAC patients. Tumor expressing high levels of MOR show higher rates of perineural invasion. Conclusion: MOR is not an independent predictor of poor survival in stage I-III PDAC but associated with perineural invasion. Patients requiring high amounts of opioids intraoperatively show worse outcome if they are expressing high levels of MOR.